Novel peptides derived from neuropeptide Y prevent chemotherapy-induced bone marrow damage by regulating hematopoietic stem cell microenvironment. Issue 5 (3rd September 2018) - Park, Min Hee; Baek, Bosung; Jin, Hee Kyung; Bae, Jae-sung
ABSTRACT: Chemotherapy-induced bone marrow damage is accompanied by acute nerve injury in the bone marrow (BM), resulting in sensory and autonomic neuropathy. Cisplatin, a popular chemotherapy drugs, induces the impairment of hematopoietic stem cells (HSCs) and bone marrow regeneration, leading to chronic bone marrow abnormalities. Previously, we reported the protective roles of neuropeptide Y (NPY) against cisplatin-induced bone marrow impairment. In this study, we identified novel peptides, generated from full-length NPY that rescued cisplatin-induced sensory neuropathy and HSC suppression by regulating cell survival in the BM microenvironment. One of these peptides, especially, showed a better protective property against these impairments compared to that seen in full-length NPY. Therefore, we suggest the NPY sequences most effective against the chemotherapy-induced bone marrow dysfunction that could be potentially useful as therapeutic agents for patients receiving chemotherapy.